Controlling – an empirical study and proposal of a relevant model for sustainable business and development in Slovakia - Sedliačiková, Mariana; Moresová, Mária; Malá, Denisa; Rowland , Zuzana (Journal of Business Economics and Management, 2021)
The economic crisis triggered by the COVID-19 pandemic suggests that enterprises should manage their business in the wider system of public, social and environmental relations. Sustainable socially responsible business is becoming a lifeline for enterprises, they need to make the most effective decisions about the future direction. This can be achieved by interconnection of sustainable socially responsible business and controlling. Following the empirical survey research carried out using 151 Slovak enterprises the maturity of enterprises concerning the use of controlling and its financial, investment, cost, quality and personnel controlling subsystems was defined. Fisher’s f-test was used for Three-factor analysis of variance questions. The results achieved in the research showing significant differences between analyzed categories of enterprises in terms of size and their subject of business. Based on the analyses of the secondary sources and on results of the research, a framework concept of the structure of corporate controlling for Slovak enterprises was proposed which represents an innovative sustainable business model in practice, the application of which in practice will be a prerequisite for the growth of performance and financial health of enterprises.